A PRELIMINARY STUDY OF POSTURAL SAFETY AND LOW-COST ELECTROMYOGRAPHY (EMG) TOWARDS LOGISTIC WORKERS IN KUCHING SENTRAL - Mohd Azrin, Mohd Said; Mohd Hasanal, Sufri Umar; Nor Kamaliana, Khamis; Aishah, Arsad (Science International, 2020)
In lifting the heavy object, the muscles of a person are strained. The incorrect posture of liftingobjects maylead to some damage to muscles causing back pain or low back pain.This back pain is mostlyreported as musculoskeletal problems in the workplace and as individuals. The back pain of the worker can be reduced if the worker is following the DOSH Lifting Requirement.Therefore, this study isconductedto evaluate the worker's postural safety while liftingandtoinvestigate the factors that affect muscle activity by identifying muscle activation at the back of the body.The data were collectedfrom the selected logistics bus company located inKuching SentralBus Terminal, Sarawak. Thedeveloped low-cost electromyography(LCEMG)device wasused to identify the raw EMG signal of the workers. The data collected can be visualized by using App or Web-based that displayed real-time data monitoring of EMG signal through ThingSpeak. The comparablesofbody posture while lifting the heavy object with and without using the belt support among the workers at Kuching Sentral Bus Terminalwere also measuredand analyzed using Human Builder in CATIA Softwareto get RULA Analysis score.The result shows that the efficiencyof lifting withless back painwas dependent on the belt support that the worker used. It also shows that muscle activity can bereduced if the worker using the belt with the correct posture tolift an object.